Sick leave and disability pension in patients with chronic hepatitis C compared with a matched general population: a nationwide register study - Matti Sällberg; Katharina Büsch; Fredrik Hansson; Michelle Holton; Martin Lagging; Johan Westin; Jan Kövamees; Jonas Söderholm (BMJ Open)
Objective The objective of this study was to evaluate sick leave and disability pension in patients with chronic hepatitis C virus (HCV) infection as compared with a matched general population cohort.Design Retrospective register study.Setting Nationwide in Sweden.Participants This register-based study used the Swedish National Patient Register to identify working-age patients with HCV in 2012 (n=32 021) who were diagnosed between 1999 and 2007 (n=19 362). Sick leave and disability pension data were retrieved from Statistics Sweden (1994–2012), with up to five matched individuals from the general population.Primary and secondary outcome measures The primary outcome was workdays lost due to sick leave episodes (>14 days) and disability pension overall. The secondary outcome was workdays lost per subgroup of patients with chronic HCV.Results In 2012, 14% of the HCV patients had ≥1 registered sick leave episode compared with 10% in the matched comparator cohort. For disability pension benefits, results were 30% versus 8%, respectively. Overall, in 2012, 57% of patients with HCV did not have any registered workdays lost, whereas 30% were absent ≥360 days compared with 83% and 9% in the matched cohort, respectively. The mean total number of annual workdays lost in 2012 was 126 days in the HCV patient cohort compared with 40 days in the matched general population comparator cohort. Annual days lost increased from a mean of 86 days 5 years before diagnosis to 136 days during the year of diagnosis.Conclusions These results show that Swedish HCV patients used more sick days and have a higher frequency of disability pension compared with a comparator cohort from the general Swedish population. Whether earlier diagnosis of HCV and treatment might impact work absence in Sweden warrants further investigation.